A systematic review of the methods utilised to measure the relationship between cancer patients and oncologists: Implications for future research and practice. (18th December 2018) - Palmer Kelly, Elizabeth; Agne, Julia L.; Hyer, Madison; Meara, Alexa; Olsen, Griffin; Pawlik, Timothy M.
Abstract: Introduction: The patient–physician relationship is a critical component of patient‐centred health care. The patient–oncologist relationship is particularly important due to the uncertainties that surround treatment of cancer. The goal of the current review was to summarise current methodological approaches to studying the relationship between cancer patients and oncologists. Methods: A systematic review using PsychInfo, Ebsco, PubMed and Google Scholar was performed using combinations and variations of the MESH terms: "relationship, " "doctor‐patient, " and "oncology." The included studies explicitly measured the "relationship" as an independent or dependent variable. Data were extracted and analysed. Results: The 13 studies included in the review were published from 2004 to 2018. There was little agreement between studies on the definition of the patient–oncologist relationship. Trust was most frequently measured, but methods varied. Most studies evaluated the patient perspective ( n = 10). The few studies that considered the oncologist perspective did not measure their perception of the relationship. Conclusions: The current review demonstrates that current approaches used to assess the patient–oncologist relationship are inconsistent. These differences may limit our understanding of patient needs in current research and practice. Future research should focus on the use of a relational lens as a theoretical framework to assess the patient–oncologist relationship.